Pituitary Apoplexy Induced by Anticoagulant Therapy in Patient with Acute Coronary Syndrome: Laporan Kasus - Michael Johan; Handry Pangestu (PT Kalbe Farma Tbk., 2024)
Pituitary apoplexy defined as bleeding or infarct on pituitary gland often occurs in undiagnosed pituitary tumour. Mechanisms thought to trigger pituitary apoplexy are fluctuations in blood pressure, hormonal stimulation of the pituitary gland, coagulation disorders, or vascular disorders. The case is a male, aged 73 years, from India, with complaints of chest pain in the last four hours. Electrocardiography (ECG) and laboratory examination results lead to an acute coronary syndrome (ACS) event. Patients are given fondaparinux, aspirin, and clopidogrel. On the 4th day of hospitalization, the patient experienced a severe headache, projectile vomiting, and double vision. Radiological examination reveals a pituitary tumour with signs of diffuse haemorrhage compressing the optic chiasma, suggesting a pituitary tumour apoplexy. Hormone function tests show a non-functioning pituitary tumour. The blood thinners were discontinued, vitamin K and dexamethasone were given to reduce the patient symptoms. After a few days, the headaches and double vision began to improve. Head MRI showed stable mass of bleeding. Pituitary tumour may be a relative contraindication to dual antiplatelets and anticoagulants in acute coronary syndromes especially in group with renal or liver comorbidities.